Trajetórias dos imigrantes açorianos em São Paulo: processos de formação, transformação e ressignificação das representações culturais - Angelo, Elis Regina Barbosa (2011)
The focus of this research is to address the paths taken by Azorean immigrants in the state of Sao Paulo, Brazil, between 1950 and 1960, in order to recover the processes of formation, transformation and redefinition of cultural representations. A dialogue with the memories of emigration and immigration indicated the political, economical and social situation of the Azores in the period preceding those movements and gave away the reasons to why they took place. What was recovered indicates that the Holy Spirit Feast had an important catalyst role in the formation of immigrant communities established at Vila Carrão. The symbols and meanings of this feast are perceived to this day as one of the most important elements of the Azorean s immaterial culture, and have been shared by generations to the present time. This group s approach was to investigate an assembling of immigrants from their departure in the Azores, including means of transportations, relationships established prior and during the journey in terms of labor and family and finally the living conditions found in the booming city that was Sao Paulo. The dichotomy of supply versus demand and the search for people to work the factories, industries and trade, which promoted the process, is also analyzed here. The experiences in the city that welcomed them and several other elements coalesced help translate their life s trajectories, as they organized themselves in the district, how they were dispersed in Brazil and around the world, and especially how was the initiative of reestablishing ties with countrymen and building the House of the Azores, which led to the reinvention of traditions and the reformulation of the Holy Spirit Feast. By unveiling these social experiments, the reinterpretations translated a new profane-religious cultural tradition in a diverse environment that is the metropolis formed by a true mosaic of cultures